Cohort protocol: Guangzhou High-Risk Infant Cohort study. Issue 10 (16th October 2020) - Hu, Pian; Han, Azhu; Hu, Yan; Wen, Yuqi; Liang, Jingjing; Xiao, Wanqi; Lin, Suifang; Song, Yanyan; Tan, Xuying; Zhao, Xiaopeng; Dong, Haipeng; Liu, Qianyun; et al.
Abstract : Introduction: Despite the increase in the survival rate of high-risk infants (HRIs) worldwide, the prevalence of motor and neurodevelopmental sequelae in such newborns has not shown concomitant improvement. Meanwhile, there are few cohorts that explore factors related to the development of HRIs in China. Therefore, the Guangzhou High-Risk Infant Cohort (GHRIC) has been designed to examine the complex relationships among a myriad of factors influencing growth and development in such children. Methods and analysis: The GHRIC study is a prospective cohort study that by the year 2023 will enrol an estimated total of 3000 HRIs from Guangzhou Women and Children's Medical Center (GWCMC) in Guangzhou, China. This study is designed to assess the growth and cognitive characteristics of HRIs and the risk factors affecting their development and prognoses. Data on risk factors, neurodevelopmental and cognitive-function evaluations, laboratory results, and specimens will be collected and analysed. Information on perinatal and clinical interventions for these infants will also be recorded during regular follow-up visits until age 6. Ethics and dissemination: The protocol for this study has been approved by the Research Ethics Committee of GWCMC, which accepted responsibility for supervising all of the aspects of the study (No. 2017102712). Study outcomes will be disseminated through conference presentations, peer-reviewed publications, the Internet and social media. Trial registration number: ChiCTR-EOC-17013236